Zotero’s Training to Improve Citation Skills in the Preparation of Students' Final Project - Ananda, Yosep Yuswanto Tri; Samsidar, Samsidar; Nasrudin, Abdul Rohman; Sinaga, Samuel Partogi Hasudungan; Ilham; Misdar Alamsyah (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
This activity was carried out focusing on managing references using the Zotero application. The target of this training is the final semester students of the Fishery Product Technology of Nunukan State Polytechnic who are preparing for the preparation of the final project. Initial observations showed that students experienced difficulties related to reference management. This training uses a participatory approach. The stages carried out are preparation, implementation, and closing. The preparation is used to design materials and teaching materials. The implementation stage was divided into two sessions. After being given a description of the material, the speaker and the participants practiced using the Zotero. Zotero’s practice starts from the installation process to creat a bibliography. The participants were instructed to follow directly every step exemplified by the speaker. Participants can directly ask if they have difficulty following the instructions. The implementation of the training was conducive and most participants were able to participate well. Participants were able to apply citation-making in scientific papers and were able to follow directions with enthusiasm. Based on the response questionnaire, 80% stated that the Zotero training was very helpful for students to manage the references used to prepare of the final project.